Guidelines For Placement Of Product-Of-Combustion Fire Sensors In Underground Mines ? Objective (The National Institute for Occupational Safety and Health (NIOSH), 1983)
Provide a strategy for calculating optimum distribution of selected sensors for detecting underground mine fires. Approach The Bureau of Mines performed research to determine adequate distribution of product-of-combustion (POC) fire sensors within mine entries. This placement strategy would improve the miner's chances for escape by locating sensors where they would most effectively, quickly, and efficiently detect fires resulting from coal or wood combustion. Spacing of Sensors Placement strategy guidelines were based on the performance of 160 F heat sensors with ideal operating characteristics which were placed at intervals of ten feet in underground mine entries. Data obtained from full-scale mine fires were used to estimate fire sizes and alarm activation times for the heat sensors. Various equations were then developed to determine spacing requirements for any fire detection system installed in entries of varying heights, widths, and ventilation rates.